Desa Wisata Berbasis Wisata Ramah Anak di Desa Wisata Pemuteran Kabupaten Buleleng Provinsi Bali (Suatu Studi Kualitatif) - Sugiarti, Dian Pramita; Sastrawan, I Gede Anom; Ariwangsa, I Made Bayu; Putri, Nyoman Manik Mas Genitri (JURNAL DESTINASI PARIWISATA, 2020)
Tourists who come to visit Bali with their families will visit child-friendly tourist villages. The goal is that the child has a sense of security and comfort when visiting a tourist village. The experience will learn a new tourist area will increase enthusiasm and refresh children from all their activities. The identification of child- friendly tourism-based tourism villages is carried out to determine the level of safety, comfort and learning that children will get when carrying out tourism activities in the tourist village of Pemuteran, Buleleng Regency. The problem raised in this study is the identification of child-friendly tourism-based tourism villages and the identification of supporting facilities provided by tourism service providers in Pemuteran tourism village, Buleleng Regency. Keywords :   Tourist Destination, Child Friendly, Tourist Villages.